Better Decision-Making: Shared Mental Models and the Clinical Competency Committee - Edgar, Laura (J Grad Med Educ, 2021)
BACKGROUND: Shared mental models (SMMs) help groups make better decisions. Clinical competency committees (CCCs) can benefit from the development and use of SMMs in their decision-making as a way to optimize the quality and consistency of their decisions. OBJECTIVE: We reviewed the use of SMMs for decision making in graduate medical education, particularly their use in CCCs. METHODS: In May 2020, the authors conducted a narrative review of the literature related to SMMs. This review included the SMM related to teams, team functioning, CCCs, and graduate medical education. RESULTS: The literature identified the general use of SMMs, SMMs in graduate medical education, and strategies for building SMMs into the work of the CCC. Through the use of clear communication and guidelines, and a shared understanding of goals and expectations, CCCs can make better decisions. SMMs can be applied to Milestones, resident performance, assessment, and feedback. CONCLUSIONS: To ensure fair and robust decision-making, the CCC must develop and maintain SMMs through excellent communication and understanding of expectations among members.